Media Argumentation Dialectic, Persuasion, and Rhetoric - Walton, Douglas (Cambridge University Press, 2013)
What initially led me to start work on this project was the observation that the examples of fallacies and questionable argument tactics studied in textbooks of informal logic often featured examples of advertisements and political arguments of the kind that have to do with elections or with public policies. Many of them are media arguments from sources such as political speeches, commercial ads, or Internet blogs. Such arguments are especially interesting when it is evident that they were used – for example, in ads – as rhetorically effective techniques to persuade a mass audience. Formerly (and often still), such arguments tended to be classified in logic as fallacious.